MAKNA IDIOMATIS DALAM MAJALAH SUARA PENDIDIKAN EDISI OKTOBER-NOVEMBER 2018 - Irwansyah, Irwansyah (STKIP PGRI Jombang, 2019)
The researcher discusses the meaning contained in the magazine because language users often do not understand the meaning contained in written language, namely idioms. The reader is often difficult to understand because the meaning is no different with the original meaning o concept that embodies. Researchers focus the research by using three types of idioms, namely the meaning of the idiomatic based on the occurrences of idioms in the form of the mention of a part of the whole assumption, the meaning of the idiomatic based on the occurrences of idioms in the form of the mention of the material, and the meaning of idiomatic based on the type of idiom in the form of the expression. Research conducted discusses the word as material for analysis so that the required description of that detail. The research method used is descriptive qualitative because in accordance with the discussion and data sources that will be examined. According to the results of the analysis of research data about the meaning of idiomatic in Sounds magazine Education edition October-November 2018 that has been done found some kind of meaning idiomatic. The data is obtained based on the three focus that have been formulated in the focus of research. The data was found in accordance with the three focus of research, the first data are the city of santri, onde-onde city and samurai country. The second data are Plastic bags, banknotes and coins. And the third data are Baby, rising level and souvenirs.